Prospects for polar tourism - Snyder, J. M.; Snyder, J. M.; Stonehouse, B.; Stonehouse, B. (Wallingford :CABI, 2007)
This book examines polar tourism in its environmental, economic and cultural settings and explores the potential for growth as well as essential management for sustainability. It has 17 chapters organized in 4 parts under the following headings: (i) tourism and the polar environment; (ii) economic roles of polar tourism; (iii) developments in Antarctic tourism; and (iv) managing the new realities. The book will appeal to researchers in tourism, ecology and environmental studies, and to those involved in developing sustainable polar tourism. It has a subject index.
Keywords: EE115 - Natural Resource Economics, (New March 2000); EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); PP000 - Natural Resources (General); UU700 - Tourism and Travel; Antarctica; Arctic regions; polar regions